Limitations and Promise of Retinal Tissue From Human Pluripotent Stem Cells for Developing Therapies of Blindness - Singh, Ratnesh K.; Nasonkin, Igor O. (Frontiers in Cellular Neuroscience, 2020)
Abstract The self-formation of retinal tissue from pluripotent stem cells generated a tremendous promise for developing new therapies of retinal degenerative diseases, which previously seemed unattainable. Together with use of induced pluripotent stem cells or/and CRISPR-based recombineering the retinal organoid technology provided an avenue for developing models of human retinal degenerative diseases "in a dish" for studying the pathology, delineating the mechanisms and also establishing a platform for large-scale drug screening. At the same time, retinal organoids, highly resembling developing human fetal retinal tissue, are viewed as source of multipotential retinal progenitors, young photoreceptors and just the whole retinal tissue, which may be transplanted into the subretinal space with a goal of replacing patient's degenerated retina with a new retinal "patch". Both approaches (transplantation and modeling/drug screening) were projected when Yoshiki Sasai demonstrated the feasibility of deriving mammalian retinal tissue from pluripotent stem cells, and generated a lot of excitement. With further work and testing of both approaches in vitro and in vivo, a major implicit limitation has become apparent pretty quickly: the absence of the uniform layer of Retinal Pigment Epithelium (RPE) cells, which is normally present in mammalian retina, surrounds photoreceptor layer and develops and matures first. The RPE layer polarize into apical and basal sides during development and establish microvilli on the apical side, interacting with photoreceptors, nurturing photoreceptor outer segments and participating in the visual cycle by recycling 11-trans retinal (bleached pigment) back to 11-cis retinal. Retinal organoids, however, either do not have RPE layer or carry patches of RPE mostly on one side, thus directly exposing most photoreceptors in the developing organoids to neural medium. Recreation of the critical retinal niche between the apical RPE and photoreceptors, where many retinal disease mechanisms originate, is so far unattainable, imposes clear limitations on both modeling/drug screening and transplantation approaches and is a focus of investigation in many labs. Here we dissect different retinal degenerative diseases and analyze how and where retinal organoid technology can contribute the most to developing therapies even with a current limitation and absence of long and functional outer segments, supported by RPE.